To speak and be heard : seeking good government in Uganda, ca. 1500-2015 - Hanson, Holly Elisabeth (New African histories series., 2022)
"Through detailed archival research, Hanson reveals the origins of Uganda's strategies for good government-assembly, assent, and powerful gifts-and explains why East African party politics often fail"--